2012
DOI: 10.1162/jocn_a_00225
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Effects of Methylphenidate in Nonhuman Primates: Trade-offs between Cognitive and Behavioral Performance

Abstract: Low doses of methylphenidate reduce hyperactivity and improve attention in individuals with attention deficit hyperactivity disorder (ADHD) as well as in healthy humans and animals. Despite its extensive use, relatively little is known about its mechanisms of action. This study investigated the effects of methylphenidate on working memory performance, impulsivity, response accuracy and precision, and the ability to stay on task in rhesus monkeys using an oculomotor delayed response task. Methylphenidate affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 30 publications
5
37
0
Order By: Relevance
“…Lastly, we also noticed that monkey M performed particularly longer sessions following treatment. This observation is in line with that of Rajala et al (2012), however, that measure largely depends on satiety, which itself depends on several non-experimental factors more difficult to control. Nevertheless, we computed the total number of trials performed by each animal and tested whether these were significantly larger in treatment versus corresponding control sessions.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 90%
See 3 more Smart Citations
“…Lastly, we also noticed that monkey M performed particularly longer sessions following treatment. This observation is in line with that of Rajala et al (2012), however, that measure largely depends on satiety, which itself depends on several non-experimental factors more difficult to control. Nevertheless, we computed the total number of trials performed by each animal and tested whether these were significantly larger in treatment versus corresponding control sessions.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 90%
“…Conversely, more recent studies have reported enhancing effects of MPH on delayed response (Gamo et al, 2010;Rajala et al, 2012) and DMTS performance (Bain et al, 2003; but see Soto et al, 2013 as well as Hutsell andBanks, 2015). However, best-dose analyses-as used in Gamo et al (2010)-are prone to false positives (Soto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased impulsivity might be linked with impaired time perception, such that the promotion of the subjective passage of time may facilitate early impulsive responses (Wittmann and Paulus, 2008;Pine et al, 2010). Recently, correlation between impulsivity and eye movements has been shown in humans (Munoz et al, 2003;Cirilli et al, 2011;Hakvoort Schwerdtfeger et al, 2012) and monkeys (Rajala et al, 2012). In particular, Rajala et al (2014) found that the availability of DA transporter in the basal ganglia correlated with the rate of early saccades in the triggered MS task with a long delay (up to 6 s), suggesting that reduced DA might cause impulsive behavior.…”
mentioning
confidence: 99%